Maximizing efficiency: exploring the crucial role of ducts in air-cooled lithium-ion battery thermal management - Gogoi, Bonashree; Deka, Hiranya; Sharma, Prabhakar; Barik, Debabrata; Medhi, Bhaskar Jyoti; Bora, Bhaskor Jyoti; Paramasivam, Prabhu; Agbulut, Umit (SPRINGER, 2025)
The thermal management of lithium-ion battery packs (LIBP) is crucial in ensuring safe and efficient operation in electric vehicles (EVs). The major concern of LIBP is to keep it at an appropriate temperature during the energizing and draining processes. The present work reviews the critical role of duct design in enhancing the efficiency of air-cooled LIBs, by comparing symmetrical and asymmetrical duct configurations. Furthermore, the present review assesses in what way the optimized airflow distribution can significantly improve heat dissipation and temperature uniformity across battery modules. Further, works pertaining to the determination of the optimized designs of the ducts are explored with the installation of different types of augmented components for the air-cooling techniques focusing on factors, such as cooling rate, airflow resistance, and temperature gradients, using the computational fluid dynamics have been analyzed. The summary of the review concludes that symmetrical ducts not only enable more uniform temperature control but also contribute to energy savings by reducing the power required for cooling fans. Additionally, the review also highlights the potential for duct optimization as a simple, cost-effective solution for meeting the thermal management requirements in next-generation LIBPs in EVs.
Keywords: Temperature effects; Air cooling; Spoilers; Vortex generators; CFD; BTMS; ELECTRIC VEHICLES; ENERGY-STORAGE; STRUCTURE OPTIMIZATION; COOLING SYSTEM; DESIGN; PACK; PERFORMANCE; FLOW; TECHNOLOGIES; Thermodynamics; Chemistry